INTERVENSI TERHADAP SISWI UNDERACHIEVING GIFTED DI SEKOLAH INTERNASIONAL “X” BANDUNG - Linda Linda (Psibernetika, 2014)
Each child is born with a unique. A gifted child is one of the uniquenessthat needs special attention because it is not free from problems. Gifted childrenwho do not have the opportunity to develop their talents often have problems inacademic achievement or school. This research focuses on achievements of agifted child or better known as the underachieving gifted child. This study designis a single-case study with purposive sampling technique. Data were collectedfrom observation, interview, and a series of psychological tests (WISC, WZT,DAM, BAUM, and HTP). Intervention is to implement board therapy (reward anddelay of reward) consistently both at home and school.Keywords: gifted child, underachieving gifted child